2023
DOI: 10.3389/fphys.2022.1079667
|View full text |Cite
|
Sign up to set email alerts
|

Integrated metabolomics and lipidomics evaluate the alterations of flavor precursors in chicken breast muscle with white striping symptom

Abstract: White striping (WS) is the most common myopathy in the broiler chicken industry. To reveal flavor changes of WS meat objectively, flavor precursors of WS breast muscle were evaluated systematically with integrated metabolomics and lipidomics. The results showed that WS could be distinguished from normal controls by E-nose, and four volatile compounds (o-xylene, benzene, 1,3-dimethyl, 2-heptanone and 6-methyl and Acetic acid and ethyl ester) were detected as decreased compounds by gas chromatography-mass spectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…A total of 120 individuals were used for myopathy evaluation, including wooden breast (WB) and white striping (WS). WB and WS were scored and classified by subjective assessment as described in previous studies (normal breast scored 0, mild WB/WS scored 1, moderate WB/WS scored 2) [16] , [17] . Drip loss (DL) and compression force (CF) were measured as previous reports [18] , [19] .…”
Section: Methodsmentioning
confidence: 99%
“…A total of 120 individuals were used for myopathy evaluation, including wooden breast (WB) and white striping (WS). WB and WS were scored and classified by subjective assessment as described in previous studies (normal breast scored 0, mild WB/WS scored 1, moderate WB/WS scored 2) [16] , [17] . Drip loss (DL) and compression force (CF) were measured as previous reports [18] , [19] .…”
Section: Methodsmentioning
confidence: 99%
“…The breasts with white striping are also less juicy than the normal chicken breasts [68] and can be chewier [69], as they have higher toughness values, which may be due to the increase in the collagen content. Kong et al [70] discovered that in breast fillets with white striping, there is a decrease of phospholipids, which can be assumed to lead to a lower sensory aroma profile, since phospholipids have shown to increase the aroma in beef. There was also a decrease in the histidine levels, which can be assumed to decrease the palatability of breast fillets with white stripes, as histidine contributes to the taste activity value, which measures how a component contributes to the overall taste [71].…”
Section: The Effects Of White Striping On Meat Quality and Productionmentioning
confidence: 99%
“…Although its etiology is still unknown, white striping has been reported to have histological lesions, including myo-degeneration and necrosis, lymphocyte, fat, and macrophage infiltration, fibrosis, and lipidosis ( Trocino et al, 2015 ). Here, Kong and co-workers found that white striping-affected breast was distinguished from normal unaffected breast by a decreased level of E-nose, and four volatile compounds (o-xylene, benzene, 1,3-dimethyl, 2-heptanone and 6-methyl and acetic acid and ethyl ester) ( Kong et al, 2022 ). Lipidomics analyses revealed increased levels of neutral lipid and decreased phospholipids in white striping-affected muscle.…”
mentioning
confidence: 99%